Rapid method to estimate temperature changes in electronics elements - Oborskii, G. A.; Savel'eva, O. S.; Shikhireva, Yu. V. (Technology and design in electronic equipment, 2014)
Thermal behaviour of electronic equipment is the determining factor for performing rapid assessment of the effectiveness of design and operation of the equipment. The assessment method proposed in this article consists in fixation of an infrared video stream from the surface of the device and converting it into a visible flow by means of a thermal imager, splitting it into component colours and their further processing using parabolic transformation. The result of the transformation is the number used as a rapid criterion for estimation of distribution stability of heat in the equipment.